Optimization of roasting condition for soybean cake evaluated by in situ protein degradability and N-fractionation method - KUMAR, SANJAY; WALLI, T K; KUMARI, RAJNI (The Indian Journal of Animal Sciences, 2011)
The present investigation was carried out to optimize temperature of roasting of soybean over a fixed time period of 30 min to make it a bypass protein. As the temperature of roasting increased, the effective protein degradability of soybean cake decreased and a reasonably good effect was seen when soybean cake was roasted at 160°C for 30 min, as reflected by a marginal increase in UDP content of the cake at 170°C. The ADIN (acid detergent insoluble N) content of the cake also increased with the increase in the roasting temperature and there was hardly any further increase in UDP content after 160°C temperature. Protein fractionation on the basis of solubility in three solvents, namely, phosphate buffer, NDS (neutral detergent solution) and ADS (acid detergent solution) also gave the similar indication as the in situ protein degradation. As the temperature of roasting increased, A + B1 fraction which relates to RDP (rumen degradable protein) fraction decreased and correspondingly, the B2 fraction, which is the main component of UDP (undegradable dietary protein) increased. On the basis of N degradability in rumen and N solubility results, it could be concluded that the optimum roasting temperature for making soybean cake a good source of bypass protein is 160°C for 30 min.